Aerobic Exercise Training in Very Severe Chronic Obstructive Pulmonary Disease: A Systematic Review and Meta-Analysis - Paneroni, Mara; Simonelli, Carla; Vitacca, Michele; Ambrosino, Nicolino (American journal of physical medicine & rehabilitation, 2017)
To evaluate the effectiveness of exercise training in patients with very severe chronic obstructive pulmonary disease (COPD). We searched MEDLINE, EMBASE, Cochrane Central Register of Controlled Trials, and Cumulative Index to Nursing and Allied Health Literature databases using the following as search terms: COPD, Chronic Obstructive Pulmonary Disease, Exercise, and Pulmonary Rehabilitation. We included randomized controlled trials (RCTs) of subjects with forced expiratory volume in the first second of less than 35% of the predicted normal value enrolled in in-patient, outpatient, or home- or community-based training programs lasting at least 4 weeks with respect to usual care. We included RCTs with outcome measures including the 6-minute walking test and/or health-related quality of life assessed by the St. George's Respiratory Questionnaire (SGRQ). Of 580 articles screened, 10 were included. The programs' duration ranged from 4 to 52 weeks with 1 to 5 sessions per week lasting 15 to 40 minutes each. The intervention group improved in 6-minute walking test [weighted mean difference, 67.1 (95% confidence interval [CI], 37.897-98.927); standardized mean difference, 3.86 (95% CI, 2.04-5.67)], and St. George's Respiratory Questionnaire [weighted mean difference, -8.041 (95% CI, -15.273 to -0.809); standardized mean difference, -1.23 (95% CI, -2.14 to -0.31)]. Exercise training improves exercise tolerance and health-related quality of life in patients with very severe COPD. However, because few studies on severely affected patients are available and the training programs are Highly heterogeneous, larger RCTs are needed.